2017
DOI: 10.1186/s40795-017-0144-4
|View full text |Cite
|
Sign up to set email alerts
|

Undernutrition: who cares? Perspectives of dietitians and older adults on undernutrition

Abstract: Background: Many older adults are at risk of undernutrition. Dietitians play a key role in the management and treatment of undernutrition, but older adults have difficulties to comply with dietetic recommendations. This qualitative study investigated which barriers older adults experience in adhering to treatment for undernutrition. Current dietetic practices and older adults' experiences were studied, and the potential to use protein-enriched regular products in undernutrition treatment was investigated. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 22 publications
2
29
1
Order By: Relevance
“…This gap in knowledge was evident both from the older people’s and carers’ perspectives. A lack of awareness was also reported by Beelen and colleagues who interviewed older people receiving treatment for undernutrition [27]. McKie and colleagues reported that older people in Scotland conceptualised healthy eating as ‘proper food’, variety, moderation and ‘an eating routine’; all notions that we also came across in our study.…”
Section: Discussionsupporting
confidence: 57%
“…This gap in knowledge was evident both from the older people’s and carers’ perspectives. A lack of awareness was also reported by Beelen and colleagues who interviewed older people receiving treatment for undernutrition [27]. McKie and colleagues reported that older people in Scotland conceptualised healthy eating as ‘proper food’, variety, moderation and ‘an eating routine’; all notions that we also came across in our study.…”
Section: Discussionsupporting
confidence: 57%
“…This may result in the inappropriate prescribing of oral nutrition supplements, a situation where a tailored approach would be better. Results from the study of Beelen et al . are similar: primary care and nursing home dietitians can sometimes feel undervalued by general practitioners, and older adults are often referred to them too late, which hampers proper nutritional care.…”
Section: Resultsmentioning
confidence: 92%
“…Eight studies were categorised regarding the attitudes of dietitians and other health professionals concerning the dietetic role . In general, other health professionals have a positive attitude to and acknowledge the importance of nutritional care for the malnourished elderly .…”
Section: Resultsmentioning
confidence: 99%
“…Dietary habits are often based on lifelong traditions, and changes in diet can be difficult for older adults. Individualising suggestions with reference to the patient's dietary habits is therefore recommended (Beelen et al, ; Locher et al, ). The diet recording in the app revealed or highlighted challenges related to nutrition.…”
Section: Discussionmentioning
confidence: 99%